Vacancy referrals, job search, and the duration of unemployment: a randomized experiment - Per Engström; Patrik Hesselius; Bertil Holmlund (Center for Economic Studies and ifo Institute (CESifo), 2009)
One goal of the public employment service is to facilitate matching between unemployed job seekers and job vacancies; another goal is to monitor job search so as to bring search efforts among the unemployed in line with search requirements. The referral of job seekers to vacancies is one instrument used for these purposes. We report results from a randomized Swedish experiment where the outcome of referrals is examined. To what extent do unemployed individuals actually apply for the jobs they are referred to? Does information to job seekers about increased monitoring affect the probability of applying and the probability of leaving unemployment? The experiment indicates that a relatively large fraction (one third) of the referrals do not result in job applications. Information about intensified monitoring causes an increase in the probability of job application, especially among young people. However, we find no significant impact on the duration of unemployment.
Keywords: C99; J64; J68; 330; Vacancy referral; job matching; job search; randomized experiment; Arbeitsuche; Arbeitsvermittlung; Arbeitslosigkeit; Test; Schweden